2014
DOI: 10.1016/j.baae.2014.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Invasion by Solidago species has limited impacts on soil seed bank communities

Abstract: Increasing attention in invasion biology is being paid to measuring and understanding the impacts of invasive species. For plant invasions, however, the impact of invasion on soil seed bank communities has been under-studied. At six sites in southern Germany, we investigated whether areas invaded by Solidago gigantea and Solidago canadensis experienced a reduction in seed bank species richness, size and diversity, and a change in species composition compared to adjacent uninvaded areas. We found no overall eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 13 publications
(16 reference statements)
2
13
0
Order By: Relevance
“…The extent of the reduction in both seedling density (60%) and in the number of plant species (30%) are in the range reported for the impact of perennial invasive plant species on soil seed banks (Gioria et al 2012). As a general pattern, perennial invasive plants seem to affect different components of the soil seed bank in a similar way (Gioria & Osborne 2009;Gioria et al 2012), although some recent studies indicated that several perennial invasive plants do not affect the density of seedlings and species richness in the soil seed bank (Abella, Chiquoine, & Vanier 2013;Chenot et al 2014;Kundel, van Kleunen, & Dawson 2014). Available evidence indicates that annual invasive plants show species-specific effects on the soil seed bank.…”
Section: Soil Seed Bankmentioning
confidence: 92%
“…The extent of the reduction in both seedling density (60%) and in the number of plant species (30%) are in the range reported for the impact of perennial invasive plant species on soil seed banks (Gioria et al 2012). As a general pattern, perennial invasive plants seem to affect different components of the soil seed bank in a similar way (Gioria & Osborne 2009;Gioria et al 2012), although some recent studies indicated that several perennial invasive plants do not affect the density of seedlings and species richness in the soil seed bank (Abella, Chiquoine, & Vanier 2013;Chenot et al 2014;Kundel, van Kleunen, & Dawson 2014). Available evidence indicates that annual invasive plants show species-specific effects on the soil seed bank.…”
Section: Soil Seed Bankmentioning
confidence: 92%
“…In China, the species was first recorded in the east, in Shanghai, in 1935, and spread from there to the west, north and south of China, where it is now widely distributed (Dong et al 2006;Lu et al 2007). Extensive clonal growth of S. canadensis leads to dense stands of shoots, which reduces native species diversity (Dong et al 2006), but without apparent impact on the native soil seed bank (Kundel et al 2014). Its seeds are small, numerous and wind dispersed, which facilitates long-distance dispersal (Dong et al 2006).…”
Section: Study Speciesmentioning
confidence: 99%
“…Temperature is a key environmental factor regulating dormancy and germination. During seed maturation, temperature influences innate dormancy, and when seeds become a part of the soil seed bank, temperature and moisture content are the key factors that regulate and synchronize the dormancy cycle across seasons (Kendall and Penfield 2012;Kundel et al 2014;Nambara et al 2010).…”
Section: Introductionmentioning
confidence: 99%